1998
DOI: 10.1007/bf03178082
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Limited Adaptive Histogram Equalization image processing to improve the detection of simulated spiculations in dense mammograms

Abstract: The purpose of this project was to determine whether Contrast Limited Adaptive Histogram Equalization (CLAHE)improves detection of simulated spiculations in dense mammograms. Lines simulating the appearance of spiculations, a common marker of malignancy when visualized with masses, were embedded in dense mammograms digitized at 50 micron pixels, 12 bits deep. Film images with no CLAHE applied were compared to film images with nine different combinations of clip levels and region sizes applied. A simulated spic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
239
0
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 585 publications
(277 citation statements)
references
References 18 publications
1
239
0
10
Order By: Relevance
“…17 The clinical trial found that the speed and accuracy of readings using the Mammoview softcopy display were not significantly different from readings of the same cases by the same observers using film display. The softcopy reading times, while not statistically significantly different, were slightly faster than those for film.…”
Section: Clinical Trial Main Results: Same Speed and Accuracymentioning
confidence: 91%
See 1 more Smart Citation
“…17 The clinical trial found that the speed and accuracy of readings using the Mammoview softcopy display were not significantly different from readings of the same cases by the same observers using film display. The softcopy reading times, while not statistically significantly different, were slightly faster than those for film.…”
Section: Clinical Trial Main Results: Same Speed and Accuracymentioning
confidence: 91%
“…17 The correlation of interactions with review time, with the larger number of interactions causing longer review times, would logically be expected. This supports the choice of simple and easy to use interfaces, as well as simplifying mental modes and operations.…”
Section: Main Analysismentioning
confidence: 99%
“…To estimate the number of blobs which correspond to PM 10 or greater air particles trapped on the petroleum jelly layer of the test surface, well-established image processing and computer vision techniques are run. Such algorithms involve Otsu's method for thresholding [26], Contrast Limited Adaptive Histogram Equalization-CLAHE [27], and Moore's tracing algorithm for extracting. of at least ×12 magnification.…”
Section: Design Of Guidelines For Low-cost Air Quality Sensing Devicesmentioning
confidence: 99%
“…The enhanced image often does not c 2013 NSP Natural Sciences Publishing Cor. look natural and is disturbing [16]. …”
Section: Contrast-limited Adaptive Histogram Equalization (Clahe)mentioning
confidence: 99%